The Ability of Respiratory Commensal Bacteria to Beneficially Modulate the Lung Innate Immune Response Is a Strain Dependent Characteristic - Ortiz Moyano, Francisco Ramiro (2020)
We investigated whether the ability of commensal respiratory bacteria to modulate the innate immune response against bacterial and viral pathogens was a shared or strain-specific characteristic. Bacterial strains belonging to the Corynebacterium pseudodiphtheriticum and Dolosigranulum pigrum species were compared by studying their influence in the Toll-like receptor (TLR)-2- and TLR3-triggered immune responses in the respiratory tract, as well as in the resistance to Respiratory Syncytial Virus (RSV) and Streptococcus pneumoniae infections. We demonstrated that nasally administered C. pseudodiphteriticum 090104 or D. pigrum 040417 were able to modulate respiratory immunity and increase the resistance against pathogens, while other strains of the same species did not influence the respiratory immune responses, demonstrating a clear strain-dependent immunomodulatory effect of respiratory commensal bacteria. We also reported here that bacterium-like particles (BLP) and cell walls derived from immunomodulatory respiratory commensal bacteria are an interesting alternative for the modulation of the respiratory immune system. Our study is a step forward in the positioning of certain strains of respiratory commensal bacteria as next-generation probiotics for the respiratory tract.